Occurrence, Profile, and Potential Risks of Novel and Legacy Polyfluoroalkyl Substances in Bullfrogs: Pilot Study in an Intensive Aquaculture Region, China - Sun, Qiongping; Xiong, Yonglong; Bi, Ran; Zhan, Xinyi; Fan, Yueyao; Su, Chuanghong; Chen, Zhenwei; Zheng, Zhao; Diao, Jieyi; Wang, Tieyu (Frontiers in Environmental Science, 2021)
Per- and polyfluoroalkyl substances (PFASs) have captured worldwide attention due to their persistent and bioaccumulative characteristics. The bullfrog was a kind of high nutritious and edible aquatic products, nevertheless, its accumulation characteristics of PFAS had not been paid attention. The present study analyzed the PFAS concentrations in different tissues of cultured bullfrogs and relevant water, sediments collected from aquaculture region in the coastal area of South China. The rResults showed that total PFAS concentrations were 50.26 - 364.25 ng/L in water, with a mean of 135.58 ng/L, thereinto, that in effluent water were significantly higher significantly than those in influent water, which means bullfrog farming could increase contaminants into the surroundings. The total PFAS concentrations varied from 2.89 to 162.26 ng/g·dw in sediment. The distribution profile of PFASs in sediment was similar to that of water, with short-chain playing a significant role. The tTotal PFASs in bullfrog tissues were 3.36-84.07 ng/g·dw with the highest values in digestive system (intestines and stomach). As for one novel PFAS alternative, chlorinated polyfluorinated ether sulfonate (F-53B), which was found at high detectable levels in all habitat samples, and higher value of logarithmic bioaccumulation factors. The estimated dietary intake (EDI) for residents in study area was generally higher than that in other regions, however, the hazard ratios (HRs) for most detected PFASs were far below the safety threshold value “1”. These results suggest that frequent consumption of these bullfrogs would basically not cause severe health effects on local residents in terms of PFASs.